Pengaruh Likuiditas, Struktur Modal, dan Risiko Operasional terhadap Kinerja Keuangan Dimoderasi Ukuran Perusahaan - Okpianti, Theodora Okpianti; Indah, Djunita Permata; Astarani, Juanda (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
This study aims to explain the effect of liquidity risk, capital structure, and operational risk on financial performance, with firm size as a moderating variable. Quantitative methods are used with secondary data from the annual financial reports of conventional banks listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The sample was selected using purposive sampling, and the analysis was carried out through regression moderation with EViews 12 software. The results of this study indicate that liquidity risk has a positive effect on financial performance, while capital structure and operational risk show no effect. In addition, company size has been shown to moderate and play a role in strengthening the relationship between liquidity risk, capital structure, and operational risk with financial performance. These findings prove that good liquidity management and a large company scale can increase bank profitability.